Cliff Failure Processes and Longshore Dispersal of Sediments, Vrgada Island (Croatia): Input from SFM Photogrammetryand Sediment Characteristics - Furcic, Nina; Pikelj, Kristina; Marković, Frane (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2024)
The coastal cliff on the Vrgada island is developed in Pleistocene aeolian-alluvial deposits which are subject to constant erosion. Digital Structure-from-Motion photogrammetry has been used to record and monitor the erosion of the cliff most of which occurs in the form of rockfalls. As a result, an L-shaped beach has formed. The eroded material is reworked and partially washed away by rain and waves. The prevailing waves are generated by the Scirocco wind (SE, and they transport the eroded material from the eastern to the north-western part of the beach. This transport direction is confirmed by heavy mineral analysis, including grain size, and by the carbonate content of the beach sediments. It is expected that the local input of terrigenous sediment may affect seagrass meadows and waterways. Continued erosion of the Vrgada cliff could jeopardize anthropogenic infrastructure and alter the island's coastline in the future.